Factors associated with the prevalence of hypovitaminosis D in pregnant women and their newborns - Elizabeth Blarduni; Arantzazu Arrospide; Mar Galar; Luis Castaño; Javier Mar (Elsevier, 2019)
Background: The finding of hypovitaminosis in pregnancy D has prompted the debate about its supplementation. The objective of the study was to measure the prevalence of hypovitaminosis D in mothers and newborns. Methods: A one-year observational study was conducted including the measuring of vitamin D levels in mothers and in the umbilical cord blood of newborns. An analysis was made of the variables as regards maternal characteristics, delivery and sun exposure. Results: Values lower than 20 ng/mL were found in 64.4% of 745 mothers and 41.3% of 560 newborns, and less than 30 ng/mL in 88.7% and 67.1%, respectively. Mean levels were higher in summer-autumn than in winter-spring (21.73 and 13.70 ng/mL in mothers and 29.04 and 20.49 ng/mL in cord), and higher in the umbilical cord than in the maternal plasma. Multiple pregnancies (OR: 6.29) and non-European origin (OR: 13.09) were risk factors for maternal hypovitaminosis, while maternal supplementation (OR: 0.19), physical activity (OR: 0.57), and sun exposure (OR: 0.46) had a preventive effect. Conclusions: The high rates of hypovitaminosis support the policy of giving dietary supplements to newborns. The high level of hypovitaminosis found supports the extension of screening and supplementation to all pregnant women, and not only to those with risk factors. The greater difference between mothers and newborns in seasons of low sun exposure can be interpreted as a protective effect. Resumen: Introducción: El hallazgo de hipovitaminosis D en el embarazo ha impulsado el debate acerca de su suplementación. El objetivo del estudio fue medir la prevalencia de hipovitaminosis D en gestantes y recién nacidos. Métodos: Se realizó un estudio observacional de un año de duración midiendo los niveles de vitamina D en madres y en sangre de cordón umbilical de recién nacidos. Se registraron variables relacionadas con las características de la madre, el parto y la exposición al sol. Resultados: Se encontraron valores menores de 20 ng/ml en el 64,4% de 745 madres y el 41,3% de 560 recién nacidos y menores de 30 ng/ml en el 88,7% y 67,1% respectivamente. Los niveles medios fueron más altos en verano-otoño que en invierno-primavera (21,73 y 13,70 ng/ml en madres y 29,04 y 20,49 ng/ml en cordón) y mayores en el cordón umbilical que en el plasma materno. Los embarazos múltiples (OR: 6,29) y el origen no europeo (OR: 13,09) fueron factores de riesgo de hipovitaminosis materna mientras que la suplementación materna (OR: 0,19), la actividad física (OR: 0,57) y la exposición al sol (OR: 0,46) tuvieron un efecto preventivo. Conclusiones: Las altas tasas de hipovitaminosis respaldan la política de dar suplementos dietéticos a los recién nacidos. El alto nivel de hipovitaminosis encontrado apoya la extensión del cribado y suplementación a todas las embarazadas y no solamente a aquellas con factores de riesgo. La mayor diferencia entre madre e hijo en las temporadas de baja exposición solar puede interpretarse como un efecto protector.